Pengadaan Tanah Untuk Pembangunan Pembangkit Listrik Tenaga Panas Bumi Di Solok Selatan - Syahputra, Julfahmi; Warman, Kurnia; Rosari, Anton (Lareh Law Review, 2024)
Utilization of natural resources in Indonesia for the greatest prosperity of the people is a necessity. One of the safe resources that can be utilized and has great potential is geothermal energy. However, its use requires land. The results of this research refer to land acquisition for geothermal exploitation in South Solok by providing information to the community regarding development plans, initial location data collection and public consultation. In the process of buying and selling, exchanging, or other methods agreed voluntarily by interested parties, it is carried out with a compensation mechanism and scheme determined by a committee formed by the company which will then be submitted and determined in deliberation. The conclusion in this research is that the provision of land needs carried out by PT Supreme Energy Muara Laboh refers to Presidential Decree No. 36 of 2005, Presidential Decree 36 of 2006 and the RTRW of South Solok Regency. Apart from that, in terms of the implementation of the sales and purchase process carried out by PT Supreme Energy Muara Laboh through a compensation mechanism, the name of the scheme created is "profit compensation" presented by the company.